Updates and Challenges in the Professional Development of Faculty Members: A Case Study at Okmin University - Padalulu, Levi; Malyo, Tirianus (Jurnal Ilmiah Mandala Education (JIME), 2024)
This article explores updates and challenges in the development of the teaching profession, focusing on a case study at Okmin University. Emphasis is placed on updates in teaching methods, educational technology, and modern academic demands. The study delves into the positive impacts of innovations in teaching, including technology integration, and curriculum adjustments to cater to the needs of contemporary students. Additionally, the updates encompass professional development strategies for educators through training and interdisciplinary collaboration. Simultaneously, the article highlights the challenges faced by faculty members, such as increasing workloads, demanding research expectations, and adaptation to the changing dynamics of the educational environment. Discussion on institutional support and policies that facilitate faculty development is also a critical focus in addressing these challenges. In conclusion, the evolution of the teaching profession must be accompanied by strategies to overcome challenges, enabling educators to contribute maximally to shaping a high-quality next generation while supporting the sustainability of their professional development.